The thin line between protection and conviction: Experiences with child protection services and later criminal convictions among a population of adolescents. (21st December 2017) - Alain, Marc; Marcotte, Julie; Desrosiers, Julie; Turcotte, Daniel; Lafortune, Denis
ABSTRACT: Relying on official data provided by the Québec City Youth Center, Canada, we explore the nature and intensity of officially known criminality for all youth (N = 5399) found guilty under the provisions of the Youth Criminal Justice Act between 2003 and 2012 and assess the relationship between criminality and previous episodes of child maltreatment. This article proposes to further verify the general hypothesis stating that there are empirical links between these two phenomena. The results suggest that those youth victims of specific types of child maltreatment (physical abuse, sexual abuse) seem to be found guilty of criminal acts that are significantly in line with these earlier episodes of maltreatment. These results might help to prevent potential occurrences of such a phenomenon and also contributes to the ongoing development of psychological and criminological theories assessing why and to what extent a child victim of maltreatment might later commit criminal offenses.